Prototype Design of Ergo-Flexibility Wheelchair Based on Stakeholder Technical Requirements, Zachman Framework Approach, and Nigel Cross Method Integration - Setiawan, Heri; Budiyanto, Tri; Rinamurti, Micheline; Budiarto, Dominikus; Dicka Pratama, Yohanes; Alfian, Achmad (Spektrum Industri, 2025)
The increasing demand for ergonomic and flexible wheelchairs in Indonesia highlights the need for innovation that meets both user needs and national standards. Most wheelchairs circulating in the domestic market are low-cost imported products that do not comply with the ISO 7176 series SNI 09-4663-1998 medical device standard, leading to concerns over safety and quality assurance. This study aims to design an ergo-flexibility wheelchair prototype based on stakeholder technical requirements while identifying gaps in the existing standards to improve product competitiveness and user protection. The research integrates the Zachman Framework according to the FACTS stages with the Nigel Cross seven-step design method. Data were collected through observation, in-depth interviews, and participatory ergonomics focus group discussions. The data analysis employed the Inter-Rater Reliability (IRR) method to determine stakeholder agreement levels. The findings identified seven key technical parameters, stability, maneuverability, mobility, dimensions, strength, durability, and product information, that are essential for wheelchair standardization. The mapping analysis revealed that the current SNI standard primarily emphasizes product strength through drop testing, while other ergonomic and safety factors remain unaddressed. From the evaluation of three design alternatives, Alternative 2 was selected, featuring aluminum material, dimensions of 1000 mm (L), 620 mm (W), and 910 mm (H), a foldable transport design, semi-manual manufacturing, and a weight of 12 kg with an 80 kg load capacity. Prototype testing using a roll machine and static load confirmed its structural reliability and ergonomic performance. The research contributes to advancing national wheelchair standards by integrating stakeholder-driven design parameters, promoting local innovation, and enhancing the competitiveness of Indonesian medical devices.